The decree Apostolicam actuositatem, Highlights of Vatican II’s teaching on Laity - Goyret, Philip (Annales theologici, 2017)
In context of the 50th anniversary of the publication of Apostolicam actuositatem, the article focuses on the innovative elements of this Decree. At first, the author reviews, briefly, the history of the term “laity” and the situation of the laity in the period immediately prior to Vatican II. Skipping the genesis of the Decree during the conciliar assembly, the article goes directly to the analysis of the final text, emphasizing its dependence on Lumen Gentium, and its new way of understanding the apostolate, the Church’s mission and lay spirituality. A particular underlining receives, later, the consideration of the lay person as subject of apostolic action, and the establishment of the temporal order as its specific field.